Autoantibodies against zinc transporter 8 further stratify the autoantibody‐defined risk for type 1 diabetes in a general population of schoolchildren and have distinctive isoform binding patterns in different forms of autoimmune diabetes: results from the Karlsburg Type 1 Diabetes Risk Study. Issue 2 (28th November 2020) - Baumann, K.; Kesselring, K.; Lampasona, V.; Walschus, U.; Kerner, W.; Wassmuth, R.; Schlosser, M.
Abstract: Aims: To evaluate the diagnostic relevance of autoantibodies against zinc transporter 8 (ZnT8) in schoolchildren from the general population as well as in people with autoimmune diabetes. Methods: A total of 137 schoolchildren positive for at least one of the three major diabetes‐associated autoantibodies, without diabetes heredity or preselection on HLA typing, from the Karlsburg Type 1 Diabetes Risk Study, as well as 102 people at type 1 diabetes onset, 88 people with latent autoimmune diabetes in adults and 119 people with type 2 diabetes, were analysed for different ZnT8 autoantibody variants. Results: Zinc transporter 8 autoantibody positivity was found in 18% of autoantibody‐positive schoolchildren, with a noticeable association with other autoantibodies associated with type 1 diabetes and disease progression. Furthermore, ZnT8 autoantibody positivity was associated with diabetes progression in schoolchildren positive for autoantibodies against insulinoma‐associated antigen‐2 (IA‐2) and, importantly, in seven IA‐2 autoantibody‐negative schoolchildren. Additionally, ZnT8 autoantibodies were found in 56% of people with type 1 diabetes, predominantly directed against all three ZnT8 variants and comparable to schoolchildren with multiple autoantibodies. In contrast, ZnT8 autoantibodies were detected in 10% of people with latent autoimmune diabetes in adults, none of them with reactivity to all three isoforms. Conclusion: Zinc transporter 8 autoantibodies are useful markers for prediction of type 1 diabetes in a general population, further stratifying the risk of progression in autoantibody‐positive children. ZnT8 autoantibodies are also important markers in adult‐onset diabetes, with a completely different reaction pattern in type 1 diabetes in comparison to latent autoimmune diabetes in adults, and may therefore help to differentiate between the two forms.